Documenting a historic mounted fin whale skeleton in preparation for a move: a case study at the Museu de Ciències Naturals de Barcelona - Pérez-Azcárate, Marta; Font-Rosselló, Bernat; Garcia-Franquesa, Eulàlia (2019)
In 2009, theMuseu de Ciències Naturals de Barcelona launched a new permanent exhibit that included removal and restoration of a landmark piece, a fin whale skeleton, and complete redesign of its assembly structure. In this paper we present the process and results of documenting the piece before the dismantling procedure. A graphic record was created as part of the restoration process, which secondarily served as an important source of information for designing the new mounting system. A detailed visual examination of the skeleton revealed problems in the preservation of the bone. The results of the preparatory examinations proved useful for planning a new preventive conservation program for the piece in its new location. Key words.—dismantling, documentation, mount, whale, preventive conservation, skeleton. In 2009, theMuseu de Ciències Naturals de Barcelona launched a new permanent exhibit that included removal and restoration of a landmark piece, a fin whale skeleton, and complete redesign of its assembly structure. In this paper we present the process and results of documenting the piece before the dismantling procedure. A graphic record was created as part of the restoration process, which secondarily served as an important source of information for designing the new mounting system. A detailed visual examination of the skeleton revealed problems in the preservation of the bone. The results of the preparatory examinations proved useful for planning a new preventive conservation program for the piece in its new location. Key words.—dismantling, documentation, mount, whale, preventive conservation, skeleton. In 2009, theMuseu de Ciències Naturals de Barcelona launched a new permanent exhibit that included removal and restoration of a landmark piece, a fin whale skeleton, and complete redesign of its assembly structure. In this paper we present the process and results of documenting the piece before the dismantling procedure. A graphic record was created as part of the restoration process, which secondarily ...